REPODUCTIVE PERFORMANCE OF FEMALE HORSE AT PRAIBOKUL TANARARA VILLAGE WEST MATAWAI LA PAWU OF SUMBA TIMUR REGENCY - Reni Ratni Dapawole (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The aim of this study was conducted to investigate the reproductive performances of working mare at Praibokul Tanarara Village Sub District Matawai La Pawu Of Sumba Timur Regency. The material used as the acceptors were 78 young female horse. The young female horses were used in the study belonged 50 respondens who lived in the Praibokul Tanarara village. The parameters used to observed the first mating age of young female horses were the service per conception (S/C) and foaling interval (FI). The data collected were analyzed descriptively. It analyzed and described the process of service per conception and foaling interval of the female horses. The result in this research showed that the average value of first mating age of horse female aged 2,5 years of S/C was 3 times and FI was 17 months. In otherwords, the the foaling of interval of young female horses took almost 17 months of their age. The conclucion of this research was that the young female horses at Praibokul Tanarara Village West Matawai La Pawu Of Sumba Timur Regency was generally less than the normal performance ofreproductive of horses in common . The young female horses actually need to have more normal performance in reproduction in this young age